Assessment and prioritisation of risks and SCRM strategies in Indian small and medium enterprises (SMEs) supply chains': a SCRM-AHP model. (29th September 2021) - Babu, Harish; Bhardwaj, Prabhas; Agrawal, A.K.
In the current scenario, risk management is an important aspect of every organisation. It is not confined to a particular functional area like finance, enterprise risk management etc. Hence, is equally important to mitigate the risk in the supply chain. Due to different levels of impact and different probability of occurrence, some risks have significant consequences, while others have negligible. Therefore, it is essential for supply chain managers to determine the priority of each supply chain risk while selecting the appropriate risk strategy. This makes supply chain risk management (SCRM) essential for proactive planning of supply chain risks. In this research, AHP methodology is used to provide a comprehensive understanding of assessing significant supply chain risks and prioritisation of SCRM strategies in the context of Indian SMEs. Furthermore, the results of this research also contribute to develop a conceptual framework for researchers and academia.